Dual-Specific Protein and Lipid Phosphatase PTEN and Its Biological Functions - Tu, Taojian (Cold Spring Harb Perspect Med, 2020)
Phosphatase and tensin homolog deleted on chromosome 10 (PTEN) encodes a 403-amino acid protein with an amino-terminal domain that shares sequence homology with the actin-binding protein tensin and the putative tyrosine-protein phosphatase auxilin. Crystal structure analysis of PTEN has revealed a C2 domain that binds to phospholipids in membranes and a phosphatase domain that displays dual-specific activity toward both tyrosine (Y), serine (S)/threonine (T), as well as lipid substrates in vitro. Characterized primarily as a lipid phosphatase, PTEN plays important roles in multiple cellular processes including cell growth/survival as well as metabolism.